Hubungan Pengetahuan Orang Tua dengan Kunjungan Rujukan UKGS Anak Kelas Selektif SDN Ciwedus I ke BP Gigi UPTD Puskesmas Cilegon - Maryuli, Maryuli (THERA-DENT (jurnal terapis gigi dan mulut), 2024)
Background: Dental and oral health plays an important role in supporting overall body health, especially in school-age children. Knowledge is one of the factors that can influence a person's behavior, with this knowledge can broaden understanding. UKGS is a public health effort aimed at maintaining, improving the dental and oral health of all students in schools under the guidance of the health center where the school is located in the health center's working area. Research Objective: To analyze the relationship between parental knowledge and UKGS referral visits for selective grade children at SDN Ciwedus I to the Dental BP UPTD Cilegon Health Center, Cilegon City. Method: The type of research used in this study is quantitative research using a cross-sectional design. The sample in this study was 72 respondents who were taken using a purposive sampling technique. The measuring instrument in this study used a questionnaire sheet consisting of 20 knowledge questions and a child's dental examination sheet. Data analysis used the Spearman correlation test. Results: Data analysis was carried out using the Spearman test, obtaining a p value = 0.025 (<0.05) with a correlation coefficient of 0.024. Meanwhile, parents who have good knowledge are 41.7%, sufficient knowledge is 31.9% and lack of knowledge is 26.4% and children who make referral visits to the Dental BP are 86.1% and do not make referral visits 13.9%. Conclusion: There is a significant relationship between parental knowledge and referral visits of UKGS for selective class children of SDN Ciwedus I to the Dental BP of UPTD Cilegon Health Center, Cilegon City.